Financial and Parental Stress as Predictors of Retirement Worry - Helen Kiso; Annamaria L Rudderow; Jen D. Wong (Journal of Financial Therapy, 2019)
While past studies have examined retirement planning, limited studies have investigated the role of parenthood and its influence on retirement worry. This study draws from three bodies of literature: saving for retirement, family stressors, and retirement worry. The purpose of this study was to identify key predictors of retirement worry in working-age adults with children. Specifically, it was of interest to consider child and family factors on retirement worry. A sample of 466 adults (Mage = 39.05, SD = 9.32) completed an online questionnaire. A hierarchical linear regression analysis was conducted. It was found that retirement planning measures (having clear goals and negative thoughts about retirement) as well as child and family stressors (childcare financial stress, negative work to family spillover, and having the child as a financial responsibility) predicted retirement worry. Study findings can inform programs and services aimed at assisting families in planning for retirement to avoid financial obstacles that could prevent future financial worries.
Keywords: retirement worry; childcare; financial knowledge